2007
DOI: 10.1212/01.wnl.0000259064.80564.21
|View full text |Cite
|
Sign up to set email alerts
|

Head taps evoke a crossed vestibulo-ocular reflex

Abstract: Taps to the forehead on the midline, at the hairline (Fz), with a reflex hammer or powerful bone conduction vibrator caused short-latency surface potentials from beneath both eyes in all healthy subjects. The earliest negative responses were invariably absent from the eye contralateral to the side of a previous vestibular nerve section but were preserved despite sensorineural hearing loss. These responses probably reflect vestibular function via crossed otolith-ocular pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
197
1
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(207 citation statements)
references
References 9 publications
4
197
1
5
Order By: Relevance
“…This potential is a 'crossed' reflex, i.e. recorded in the eye contralateral to the stimulated ear (Iwasaki et al, 2007), and is thought to be mediated by otolith fibres, as animal studies have shown that otolith afferents are preferentially activated by vibration and sound (Curthoys et al, 2006;Murofushi et al, 1997). As the n10 component of the reflex is abolished in patients with vestibular loss, the oVEMP has been introduced as a clinical test of otolith function.…”
Section: Introductionmentioning
confidence: 99%
“…This potential is a 'crossed' reflex, i.e. recorded in the eye contralateral to the stimulated ear (Iwasaki et al, 2007), and is thought to be mediated by otolith fibres, as animal studies have shown that otolith afferents are preferentially activated by vibration and sound (Curthoys et al, 2006;Murofushi et al, 1997). As the n10 component of the reflex is abolished in patients with vestibular loss, the oVEMP has been introduced as a clinical test of otolith function.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, the oVEMP is large [5,6] and highly lateralized, being larger on the side contralateral to the stimulated ear [7,8], important factors which contribute to its clinical utility. The lateralization of the reflex is significant as the largest oVEMPs are usually recorded using BC stimulation of the skull, which activates the vestibular receptors in both ears simultaneously.…”
Section: What Are Ovemps?mentioning
confidence: 99%
“…The lateralization of the reflex is significant as the largest oVEMPs are usually recorded using BC stimulation of the skull, which activates the vestibular receptors in both ears simultaneously. The contralateral dominance means that in patients with unilateral vestibular loss the oVEMP will be absent or attenuated on the side opposite the lesion, revealing the side of the deficit [8]. oVEMPs evoked by AC stimulation are also larger and more prevalent on the contralateral side.…”
Section: What Are Ovemps?mentioning
confidence: 99%
“…The stimuli were arranged over eight octaves from 0.5 to 64 Hz. The transient displacement stimulus waveforms consisted of cosine modulated ½ cycle (0.5 Hz), 1½ (1, 2, and 4 Hz), and 2½ cycle (8,16,32, and 64 Hz) sinusoids arranged so that at the endpoints of the motion the acceleration, the velocity and the displacement returned to zero (e.g., Fig. 2).…”
Section: Subjectsmentioning
confidence: 99%
“…For low-frequency vibration, upwards gaze also produces a large inferior response, but it is not abolished with downwards gaze, only altered in morphology, indicative of an alternative source (24). Given the role of the inferior oblique as an elevator and its particular anatomical location it is generally thought that the inferior OVEMP is produced primarily by this muscle with upwards gaze (8,18,22,30,31). Other muscles, including inferior, superior, and lateral recti have been suggested as sources for OVEMPs measured in other periocular locations and with differing gaze positions (25,30).…”
mentioning
confidence: 99%